2013
DOI: 10.1136/jnnp-2013-305532
|View full text |Cite
|
Sign up to set email alerts
|

The treatment of dystonic tremor: a systematic review

Abstract: Tremor is one of the clinical manifestations of dystonia; however, there are no specific therapeutic trials evaluating the efficacy of treatments for dystonic tremor (DT), tremor associated with dystonia or primary writing tremor (PWT). We systematically reviewed the literature available up to July 2013 on the treatment of these tremors and retrieved the data of 487 patients published in 43 papers detailing the effects of given interventions on tremor severity. Treatment outcome was highly variable, depending … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
92
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(98 citation statements)
references
References 75 publications
(77 reference statements)
2
92
0
4
Order By: Relevance
“…Anecdotal experience suggests they may be most useful for suppressing phasic aspects of dystonia, such as blinking in blepharospasm or tremor-dominant forms of dystonia. 67,81,82 They also appear to be useful in the paroxysmal dyskinesias, where dystonia can be a prominent feature. 83 Common side effects include sedation, impaired mentation and coordination, and depression.…”
Section: Treatmentmentioning
confidence: 99%
“…Anecdotal experience suggests they may be most useful for suppressing phasic aspects of dystonia, such as blinking in blepharospasm or tremor-dominant forms of dystonia. 67,81,82 They also appear to be useful in the paroxysmal dyskinesias, where dystonia can be a prominent feature. 83 Common side effects include sedation, impaired mentation and coordination, and depression.…”
Section: Treatmentmentioning
confidence: 99%
“…BT injections have a fairly accepted role in managing head tremor, tremulous spasmodic dysphonia, and primary writing tremor 8,9. However, studies of the effect of BT on other upper limb tremor types have had heterogeneous results in terms of functional disability.…”
Section: Discussionmentioning
confidence: 99%
“…Anticholinergics (ie, trihexyphenidyl, range 3-6 mg/d) produced the best result; propranolol also produced some benefit. 79 Fasano and colleagues 80 recently presented a review of 487 patients with dystonic tremor published in 43 articles and concluded that drug efficacy is generally moderate (total improvement approximately 40%), depending on the distribution and type of tremor. Anticholinergics led to approximately 40% improvement.…”
Section: Treatment Of Dystonic Limb Tremormentioning
confidence: 97%